miRNA-375 a Sensor of Glucotoxicity Is Altered in the Serum of Children with Newly Diagnosed Type 1 Diabetes - Rome, Sophie; Thivolet, Charles; Nicolino, Marc; Fabien, Nicole; Van den Hende, Kathleen; Meugnier, Emmanuelle; Jalabert, Audrey; Marchand, Lucien; Madec, Anne-Marie (Journal of Diabetes Research, 2016)
Background. The use of miRNAs as biomarkers for Type 1 Diabetes (T1D) risk is attractive as T1D is usually diagnosed in front of acute symptoms. As miR-375 is highly expressed in the endocrine pancreas, we postulated that its circulating level might reflect beta cell alterations and might be altered in the blood of T1D patients recently diagnosed. Methods. Sera were obtained from 22 T1D children at onset of the disease, before subcutaneous insulin treatment, and from 10 nondiabetic pediatric controls. MiR-375 seric level was quantified by stem-loop RT-PCR-based assay. MiRNAs regulations in isolated human islets in response to high glucose concentrations were determined by TaqMan Low-Density Array. Results. The abundance of miR-375, among the 410 miRNAs detected in human islets, mirrored its well-established role in rodent islet biology. Upregulated miRNAs targeted genes involved in islet homeostasis and regulation of beta cell mass. Downregulated miRNAs, including miR-375, were involved in pancreas secretion and protein turnover. Seric level of miR-375 was lower in T1D children versus age-matched controls, without any correlations with HbA1c, glycaemia, and number of autoantibodies. Conclusion. Altered circulating level of miR-375 at onset of T1D might be a general biomarker of metabolic alterations and inflammation associated with the disease.